2010
DOI: 10.1143/jjap.49.117001
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometric Dye Imaging for Pheochromocytoma and Cortical Neurons with a Novel Measurement System Using an Integrated Complementary Metal–Oxide–Semiconductor Imaging Device

Abstract: PACS. 64.60.-i -General studies of phase transitions.Abstract. -The concentration-induced sequence of three incommensurate phases ( , 1 , 2 ) previously disclosed in LixV2O5 are interpreted as resulting from distinct Lifshitz-invariant and Lifshitz-points instabilities. When varying the temperature, the phase displays a reentrant behavior, which is described as a folding of the high-temperature region triggered by the ordering of the lithium ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Therefore, we have been attempting to apply BpLSI to voltage-sensitive dye imaging [9]. Before potential fluorescence imaging, we firstly confirmed that voltagesensitive dye RH795 (Molecular Probes) hardly fluoresced in itself, and that BpLSI-red which had been developed to adapt for the fluorescent property of RH795 had cellular resolution Figure 6.…”
Section: Physiological Fluorescence Imaging For Primary Cultured Cmentioning
confidence: 84%
See 1 more Smart Citation
“…Therefore, we have been attempting to apply BpLSI to voltage-sensitive dye imaging [9]. Before potential fluorescence imaging, we firstly confirmed that voltagesensitive dye RH795 (Molecular Probes) hardly fluoresced in itself, and that BpLSI-red which had been developed to adapt for the fluorescent property of RH795 had cellular resolution Figure 6.…”
Section: Physiological Fluorescence Imaging For Primary Cultured Cmentioning
confidence: 84%
“…Cell culture and easy purification method for a primary culture of neural precursor/stem cells Neural precursor/stem cells were collected from the cerebral cortices of newborn mice, and purified (see [9] for detail). The neural cells were plated onto the poly-L-lysinecoated BpLSI sensor, and cultured for at least 4 weeks in all experiments to prepare mature neurons.…”
Section: A Construction and Optimization Of Imaging Systemmentioning
confidence: 99%
“…In order to address this problem, we have developed a measurement system in which an imaging device is used as a specimen dish and can directly detect the fluorescence pattern from the specimen, which is dyed by VSD. This dish imaging device enables the realization of a novel potential multi-site measurement system [6].…”
Section: Multi-site Measurement Using the Dish Image Sensormentioning
confidence: 99%
“…The surface of the device can affect living tissues or cells, and these effects can include cytotoxicity. For example, in order to culture cells on a chip, the surface must be treated, for example, by coating it with poly-L-lysine [6]. Packaging materials and/or electrode materials may be dissolved into the affected tissues Copyright c 2011 The Institute of Electronics, Information and Communication Engineers and cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation